PENINGKATAN KEMAMPUAN MENGANALISIS UNSUR INTRINSIK NASKAH DRAMA MENGGUNAKAN MODEL KOOPERATIF - Egitamersa Yolanda Br Bangun; Erikson Saragih (Fakultas Sastra Universitas Negeri Malang, 2020)
DEVELOPMENT OF COMPETENCE IN ANALYZING INTRINSIC ELEMENTS OF DRAMA TEXTS USING COOPERATIVE MODEL Abstract: The purpose of this research to improve the ability to analyze the intrinsic elements of the drama in students of class VIII-2 Private Junior High School Nurcahaya Medan using a jigsaw type cooperative learning model. The drama script is an essay containing stories or plays. The drama script is inseparable from the intrinsic element of the drama script. Jigsaw type cooperative learning model is a cooperative learning model where students work collaboratively in small groups consisting of four to six people heterogeneously. This research is a classroom action research, conducted at Private Junior High School Nurcahaya Medan. The stages of the study were divided into two cycles, each of which was implemented within the time allocation of 3x40 minutes. Subjects in this study were 33 students of class VIII-2. The data analysis technique was conducted by a qualitative descriptive analysis technique. The results of the study show an increase, i.e., in the assessment of the first cycle of 60,76 to 76,82 in the second cycle. Students who completed the first cycle were 11 students and increased to 26 students on the second cycle.Keywords: Drama script, Intrinsic element, Jigsaw, Cooperative, AbilityPENINGKATAN KEMAMPUAN MENGANALISIS UNSUR INTRINSIK NASKAH DRAMA MENGGUNAKAN MODEL KOOPERATIFAbstrak: Penelitian ini bertujuan untuk meningkatkan kecakapan siswa dalam melakukan analisis terhadap unsur pembangun naksah drama menggunakan model belajar berkelompok atau kooperatif tipe jigsaw. Naskah drama adalah karangan yang berisi cerita atau lakon. Naskah drama tidak terlepas dari unsur intrinsik naskah drama. Model pembelajaran kooperatif tipe jigsaw adalah model pembelajaran kooperatif dengan cara siswa belajar dalam kelompok kecil yang terdiri dari empat sampai enam orang secara heterogen. Penelitian ini merupakan penelitian tindakan kelas yang dilaksanakan di SMP Swasta Nurcahaya Medan. Tahap penelitian dibagi dalam dua siklus, di mana setiap siklus dilaksanakan dengan alokasi waktu 3x40 menit. Subjek pada penelitian ini adalah siswa kelas VIII-2 yang berjumlah 33 siswa. Teknik analisis data dilakukan dengan analisis deskriptif kualitatif. Hasil penelitian menunjukkan adanya peningkatan yaitu dari penilaian siklus I sebesar 60,76 meningkat menjadi 76,82 pada siklus II. Siswa yang tuntas pada siklus I sebanyak 11 siswa dan pada siklus II meningkat menjadi 26 siswa.Kata kunci: Naskah drama, Unsur intrinsik, Jigsaw, Kooperatif, Kecakapan Permalink/DOI: dx.doi.org/10.17977/um015v48i22020p148